Dynamic MRI of rat brain following manganese administration through the internal carotid artery. (July 2014) - Zhang, Run; Fa, Zhiqiang; Liu, Yi; Sun, Haitao; Li, Peng; Li, Shaorui; Wang, Xuxia; Lei, Hao; Jiang, Xiaodan
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: In this study, we investigated the dynamic distribution processes of Mn2+ in rat brain using magnetic resonance imaging (MRI) after an intra-arterial (IA) injection of MnCl2 and following the breaking of the blood–brain barrier (BBB). Methods: Adult male Sprague-Dawley (SD) rats were employed in the study. After the rats were anesthetized with urethane, 25% mannitol was administrated into the right internal carotid artery (ICA) in order to disrupt the BBB, 50 mmol/l (10 mg/kg) of MnCl2 was then injected into ICA prior to the MRI assay. The MRI was performed at 7 T for a continuous 2 hours following the administration of MnCl2. Image reconstruction and analysis were performed using the Statistical Parametric Mapping (SPM) software. Results: As time progressed, the Mn2+ enhanced signal intensity showed a gradual increase with a maximum increase at 10 minutes following MnCl2 administration, and began to decline after 10 minutes. From 30 minutes to 2 hours, the signal-enhanced region became more homogeneous, and the signal-enhanced range spread to the contralateral area up to 2 hours after MnCl2 administration. Conclusion: These results will help future research to select an appropriate time point to perform functional MRI for different types of activity-induced manganese (AIM) MRI research studies. These findings will allow researchers to discriminate intended, stimulation-specific enhanced signal from unintended, nonspecific enhanced signals.